Bio‐industrial Waste Silk Fibroin Protein and Carbon Nanotube‐Induced Carbonized Growth of One‐Dimensional ZnO‐based Bio‐nanosheets and their Enhanced Optoelectronic Properties. Issue 48 (19th July 2018) - Saravanan, Adhimoorthy; Huang, Bohr‐Ran; Kathiravan, Deepa
Abstract: High performance UV/Visible photodetectors are successfully fabricated from ZnO/fibroin protein‐carbon nanotube (ZFPCNT ) composites using a simple hydrothermal method. The as‐fabricated ZnO nanorods (ZnO NRs) and ZFPCNT nanostructures were measured under different light illuminations. The measurements showed the UV‐light photoresponse of the as‐fabricated ZFPCNT nanostructures (55, 555) to be approximately 26454 % higher than that of the as‐prepared ZnO NRs (210). This photodetector can sense photons with energies considerably smaller (2.75 eV) than the band gap of ZnO (3.22 eV). It was observed that the finest distribution of fibroin and CNT into 1D ZnO resulted in rapid electron transportation and hole recombination via carbon/nitrogen dopants from the ZFPCNT . Carbon dopants create new energy levels on the conduction band of the ZFPCNT, which reduces the barrier height to allow for charge carrier transportation under light illumination. Moreover, the nitrogen dopants increase the adsorptivity and amount of oxygen vacancies in the ZFPCNT so that it exhibits fast response/recovery times both in the dark and under light illumination. The selectivity of UV light among the other types of illumination can be ascribed to the deep‐level energy traps (ET ) of the ZFPCNT . These significant features of ZFPCNT lead to the excellent optical properties and creation of new pathways for the production of low‐cost semiconductors and bio‐waste protein based UV/Visible photodetectors. Abstract : High performance UV/visible photodetectors from ZnO/fibroin protein–carbon nanotube composites using a soft chemical route. The measurements show the UV‐light photoresponse of the as‐fabricated ZFPCNT nanostructures (55, 555) to be approximately 26 454 % higher than that of the as‐prepared ZnO samples.